2004
DOI: 10.1093/brain/awh131
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of white matter regional cerebral blood flow and autoregulation in normal pressure hydrocephalus

Abstract: The mean cerebral blood flow (CBF) has generally been demonstrated to be lower in normal pressure hydrocephalus (NPH) than in normal controls. We investigated the distribution of the regional peri- and paraventricular white matter CBF (WM CBF) in NPH at baseline and during a controlled rise in intracranial pressure (ICP). Twelve patients with idiopathic NPH (mean age 69 years) underwent a CSF infusion study. CBF was measured by H2(15)O PET at baseline and then during the steady-state plateau of raised ICP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 44 publications
(48 reference statements)
10
143
0
10
Order By: Relevance
“…36 However, NIRS measures surrogates of cerebral blood flow in the mixed arterio-venous compartment in cerebral cortex located in the watershed area between the MCA and anterior cerebral artery, where, in patients with normal pressure hydrocephalus, autoregulation has been suggested to be weaker. 37 Perhaps, this is why values of TOxa are lower than Sxa (Supplementary Table 1). The two modalities measure different anatomic regions of the brain as well as different vascular beds.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…36 However, NIRS measures surrogates of cerebral blood flow in the mixed arterio-venous compartment in cerebral cortex located in the watershed area between the MCA and anterior cerebral artery, where, in patients with normal pressure hydrocephalus, autoregulation has been suggested to be weaker. 37 Perhaps, this is why values of TOxa are lower than Sxa (Supplementary Table 1). The two modalities measure different anatomic regions of the brain as well as different vascular beds.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…82,90) In a study measuring CBF in 31 patients of suspected Chapter 1: Diagnosis iNPH with 99m Tc-HMPAO SPECT, 54B) reduced blood flow over a wide area, especially in the cortex and subcortical white matter of the frontal and temporal lobes (expansion of central low-flow area), is seen. These findings are supported by other studies.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…57,70,74,76,117,128) A PET study reported the mean CBF decreased in the cerebrum and cerebellum with regional decrease in the basal ganglia and thalamus but not in the white matter. 82) There are few studies supporting the correlation between reduced flow and degree of symptoms. 57) There are many studies showing an association between improved symptoms and increased CBF after shunt procedure, 54B,70,74,118,128) but the contradictory result has been reported.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The significant decrease in CBF in NPH patients is considered to result from reductions in cerebral perfusion pressure and appears to be maximal in the paraventricular watershed region. 10) In contrast, significant increases in CBF were recognized after CSF diversion in the left prefrontal dorsolateral areas, right frontal premotor area, right medial prefrontal region, right frontal white matter area, and right basal ganglia. 9) On the other hand, an overlap in the CBF volumes measured between patients with NPH and normal subjects suggested that ischemia may not be a prerequisite for this condition, but instead may reflect increased superficial venous pressure in patients with NPH.…”
Section: Discussionmentioning
confidence: 94%